2002
DOI: 10.1521/aeap.14.5.318.23870
|View full text |Cite
|
Sign up to set email alerts
|

Secret Pills: HIV-Positive Patients' Experiences Taking Antiretroviral Therapy in North Carolina

Abstract: Understanding the barriers to antiretroviral adherence is a critical step in improving the effectiveness of HIV treatment and saving lives. We sought to assess, qualitatively, the experiences of HIV-positive persons taking antiretroviral therapy (ART) in North Carolina. Twenty-four people participated in one of six focus groups. A structured interview script included three questions (two open-ended) and eight probes. Each discussion was taped, transcribed, and content-analyzed. Three distinct themes emerged. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 49 publications
6
63
0
7
Order By: Relevance
“…In a study of people living with HIV in rural areas taking antiretroviral therapy, participants reported they skipped doses of medication to avoid the stigma associated with publicly taking medication that could disclose their HIV status. 25 Negative attitudes of rural health care providers also may impact people living with HIV who seek care in these areas. Discrimination in care and unwillingness to care for people living with HIV=AIDS has been found among physicians, 26 dentists, 27 and rural nurses.…”
mentioning
confidence: 99%
“…In a study of people living with HIV in rural areas taking antiretroviral therapy, participants reported they skipped doses of medication to avoid the stigma associated with publicly taking medication that could disclose their HIV status. 25 Negative attitudes of rural health care providers also may impact people living with HIV who seek care in these areas. Discrimination in care and unwillingness to care for people living with HIV=AIDS has been found among physicians, 26 dentists, 27 and rural nurses.…”
mentioning
confidence: 99%
“…8,18 There is little published research about the challenges faced by rural HIV care providers. Our review identified only two studies in which the purpose was to assess provider perceptions of challenges to care delivery.…”
mentioning
confidence: 99%
“…80 In qualitative studies, HIV-positive patients reported the usefulness of technological adherence aids, but many patients were unaware that such aids existed. 56 The incorporation of these aids into clinical practice may be warranted, given their association with adherence in this prospective study. Including standardized patient education about adherence aids during ART initiation is a practical way to introduce patients to these potentially valuable interventions.…”
Section: Discussionmentioning
confidence: 95%
“…22,27 More frequent dosing may lead to missing doses because patients have difficulty with the middle of the day dose. 56 The impact of dosing complexity on adherence can guide clinicians in selecting medication regimens and delineates a role for adherence aids to help to remind patients of midday doses. In addition, the fact that dose frequency is the only aspect of regimen complexity that affected adherence may have important implications for the development of combination pills, particularly if these medications are taken more frequently and/or are more expensive.…”
Section: Discussionmentioning
confidence: 99%